STRATEGI PENANGGULANGAN NIKAH SIRRI PADA KANTOR URUSAN AGAMA KOTA TERNATE UTARA DALAM PRESPEKTIF MASLAHAH MURSALAH - Muhammad ishky rumaf; M. Thahir Maloko; Achmad Musyahid Idrus, Musy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2022)
Analysis of the factors behind Sirri's marriage and strategies for dealing with Sirri's marriage at the KUA in North Ternate City. This type of research is qualitative with a juridical, sociological, and pedagogical approach. Data sources are primary/secondary data while data collection is observation, interviews, documentation, and reference searches. Data analysis techniques use data categorization, data reduction, grouping, data preparation, data interpretation, data verification, and concluding. The results of the research are that sirri marriage does not contradict the concept of maslahah murlahan itself, so in this case the essence of sirri marriage is based on maslahah murlah which brings harm, but sirri marriage is not recorded so it can contain many fasids